Online moral deviance: an integrative review of digital behaviors - Xu Chen; Norzihani Saharuddin; Maizura Yasin; Meng Wang (Frontiers in Psychology)
Previous studies on deviant behaviors in digital environments have predominantly focused on the concept of cyber deviance, online deviance and online deviant behavior, a broad behavioral framework encompassing diverse and varied actions. However, existing research has not systematically classified these behaviors based on their characteristics, manifestations or the degree of harm caused to target users within a moral framework. To addresses this research gap, our study systematically identifies and classifies behaviors within cyber deviance, online deviance and online deviant behavior that violate moral expectations accepted by mainstream culture in a specific society, and develops a conceptual model of online moral deviance. The proposed model provides valuable insights for effectively identifying, preventing, and addressing such deviant behaviors in digital contexts. Utilizing an integrative literature review approach, we analyzed research from the Web of Science (2020–2024) database and Google Scholar, employing core, combined, and related keywords to identify relevant studies. A total of 190 articles were selected, including key research from the past 5 years and representative studies beyond this timeframe. Moreover, our research emphasizes the importance of considering cultural, regional, and social contextual differences in refining the conceptual model. This study advocates for future research to explore representative theories that can support the mechanisms or influencing factors underlying online moral deviance, and to refine the conceptual model by clearly delineating the conceptual boundaries between different types of online deviant behavior. This study advances the research on cyber deviance and online deviance, and, in particular, offers a practical conceptual model for policymakers, educators, and parents to support moral education and foster healthy online behavior.